Progression from Candida auris Colonization Screening to Clinical Case Status, United States, 2016–2023 - Anna D. Baker (Emerging Infectious Diseases, 2025)
During 2016–2023, among 21,195 US patients who tested positive for Candida auris colonization, 6.9% were subsequently found to have a positive clinical specimen (2.8% from blood). Strategies are needed to prevent invasive C. auris infections among patients with colonization (e.g., through patient decolonization).